Incentives and Endogenous Risk Taking: A Structural View on Hedge Fund Alphas - BURASCHI, ANDREA; KOSOWSKI, ROBERT; SRITRAKUL, WORRAWAT (Journal of Finance, 2014)
ABSTRACT Hedge fund managers are subject to several nonlinear incentives: performance fee options (call); equity investors' redemption options (put); and prime broker contracts allowing for forced deleverage (put). The interaction of these option‐like incentives affects optimal leverage ex ante, depending on the distance of fund‐value from the high‐water mark. We study how these endogenous effects influence performance measures used in the literature. We show that reduced‐form measures that do not account for these features are subject to economically significant false discovery biases. The result is stronger for low‐quality funds. We propose an alternative structural methodology for conducting performance attribution in hedge funds.